Barbartemplets ovale anlæg - Mortensen, Peder (Kuml, 1956)
The Temple Oval at Barbar When the summit of the large gravel mound which covered the temple buildings at Barbar was removed in the winter of 1955 the upper edge of an oval wall, connected with the temple by a ramp of about 5 metres in length and 1 ½ in breadth, was discovered on the eastern side of the mound. In the same year some reconnaissance excavations were made at this point, and in February-March 1956 the area within the wall was excavated, bringing to light the remarkable structure (Fig. 1) which is briefly described below. Above a yellow-gray gravel stratum a floor, about 10 cms. thick and consisting of a coarse grayish plaster, was found at the base of the structure; on the eastern side this plaster gradually gave way to a softer, more claylike layer containing many pebbles. In about the centre of the western half of the structure a low platform (Fig.2A) was found, raised about 15 cms. above the floor. The platform had itself a plaster floor and was edged by a roughly circular wall formed of unshaped stones cemented together by means of a fine light plaster. The interior diameter of the circle was 1.8-2.2 metres. The wall was 10-15 cms. thick and rose a matter of 3-5 cms. above floor level. Below the platform the plaster of the floor attained its maximum thickness, insomuch as it here filled an evenly rounded hollow, about 30 cms. deep, dug into the yellow gravel stratum. In association with the platform and towards the west a rectangular block of plaster was found (Fig. 2B), about 1.6 metres long and holding the impression left by three large stones, the area of which had been about 25 X 40 cms. It is possible that the plaster block originally served as a low table, or else, if the missing stones were very flat and thereby reached the same height as the circular wall, it may have formed a sort of step in front of the platform. These features, the platform and the rectangular plaster block, were surrounded by a low, almost circular wall with a diameter of 6.5-7.5 metres (Fig. 2C). The wall was 40-45 cms. broad and rose to a maximum height of 20-25 cms. above the plaster floor. Like the wall that edged the platform, it was formed of rough stones set in fine-grained plaster. The wall was best preserved to the west and to the north east; elsewhere only its impression could be seen in the plaster floor, or else all trace of it was destroyed. To the west was an opening in the wall which here was built into the lowest step of the ramp (Fig. 2D). This step was roughly made in plaster which still bears the impress of the master-builder’s - or a slave’s - hands. The lowest plaster floor was partly covered by a gray-black powderish layer, most probably waterlaid as a very fine horizontal stratification could be observed. Towards the south the layer was about 15 cms. thick, to the north only a couple of cms., as the floor here lay 15-20 cms. higher than in the south. This stratified deposit presumably covered parts of the earliest wall, which resulted partly in the laying of a new plaster floor, and partly in a raising of the height of the southern part of the outer circular wall, the building of a new wall in a northeast-southwest direction, the digging of a drainage channel, and perhaps in a slight raising of the height of the ramp. The new plaster floor had been very thin and was only preserved at a few points. Associated with the floor are a raising of the height of the outer circular wall in the south side (Fig. 2E) and a straight section of walling, about 6 metres long and running in a northeast-southwesterly direction (Fig. 2F); both these walls correspond exactly in width, height and construction with the lowest circular wall. At the western end of the straight stretch of wall stands an almost cubical block of plaster, measuring about 60 cms. in all directions (Fig. 2G). lts top appears to have originally been smoothly rounded, but it is now broken into an irregular contour, while at its foot scattered fragments of plaster were found which presumably originally formed part of the block. At the southeastern end of the oval portions of a drain were preserved, 10-15 cms. deep and 5-10 cms. wide but very irregularly shaped, its walls and bottom consisting of grayish plaster. The drain was laid in the gray-black layer and only fragments of it survived as it had been destroyed in the course of later digging on the same site. It was originally covered, and its purpose was, undoubtedly, to drain off water from the oval, the floor of which probably lay at that period at a lower level than its surroundings. Above the lowest plaster step of the ramp there was a layer of yellowish plaster, about 10 cms. thick and containing flat stone chippings; it must doubtless be interpreted as a raising of the height of the ramp, the lowest step of which was now covered by the black layer. Above still another stratum of gray-black deposit, about 10 cms. thick, the outer wall, an asymmetrical oval, was built (Fig. 21). lts foot lies at a somewhat higher level than the earlier constructions, which must, in the majority of cases, have been covered by the gray-black layer at the period when the outer wall was built. A short stretch of the wall is missing to the northeast and a longer portion to the southwest. They have been removed by diggers in search of stone, whose passage is still marked by disturbances in the layers above. The thickness of the wall varies from about 50 to about 70 cms. and, where it is best preserved, it is 105 cms. high. In some places it slopes steeply inwards, and it has therefore scarcely had an original height very much above what it has at present. The lower part of the wall is formed of long stones laid in 2-3 courses (Fig. 3), the remainder consisting of stones ranging in size from a cricket hall to a football, set in a yellowish plaster with which the wall has also been coated on the outer and inner faces. Towards the west this outer oval wall is built into the side walls of the ramp, these walls being raised considerably in height at the same time as the outer oval wall was built. The construction of the upper wall of the ramp is identical with that used in the outer wall, long stones in the lower courses and smaller stones above, set in and coated with plaster. Towards the south, under this new ramp, the older wall of the ramp can be seen projecting some few cms. From this description it will be clear that it is possible to distinguish three building phases, of which the second appears to represent nothing more than a repairing of the first structures, whereas the third phase can best be interpreted as a walling in of the whole of the area partly covered by the black deposit. The two earlier structures, like the third, have both been open areas, their walls probably no higher than they are now. Within the outer oval wall there appears, above the gray-black level, a thick deposit of grayish gravel. This same layer reappears, together with the gray-black level, in the section through the eastern portion of the temple mound, where these layers prove to have been deposited while Temple II 1), the largest of the main temple’s building phases, was in use. The oval thus appears to be contemporary, in all its phases, with Temple Il, a conclusion which is supported by the fact that both the earlier and the later ramps lead up to this building. The objects found in the gray-black layer and in the lower part of the thick gray layer are of a so uniform character that they may be described here as a single whole. A large number of sherds were discovered of the red ridged pottery of the same type as that found in Barbar during the previous years’ excavations. Of particular interest were the bases, of reddish ware, of nine pottery beakers (Fig. 4), all broken just above the base; two rim-sherds, found separately, showed that the beakers had possessed a conical or slightly curved body, and that this body was wheel-turned while the bases were formed by hand. Among the potsherds some ten sherds with polished edges may be mentioned; their function is unknown. Of copper or bronze a large quantity of thin buckled sheeting and of nails was found, and in addition a tanged arrowhead, 14.6 cms. long (Fig. 5a) and a fragment of a tanged dagger, 10.5 cms. long (Fig. 5b). A few pieces of flint swarf were also found, as well as a very large number of bones. The greater part of these objects were found in the western half of the oval around the platform and the circular wall; thus all the beaker bases came to light in the area in front of the platform. Arrowheads of the same type as that found in the oval are known from predynastic graves at Ur 2), and the pottery beakers, represented by the broken-off bases, are variants of the type of which a score of specimens have previously been dug up from the first building phase of the Barbar temple 3). The type is known both from the predynastic period at Ur, where it is later replaced by more open cups 4), and from Tépé Hissar in Iran from level III B 5). If these parallels are compared with the dating previously proposed for the main phase of the Barbar temple (Temple II) 6), the period to which the oval belongs, a dating to round about the middle of the Third Millenium BC would appear to be reasonable. Turning to the question of the function of the structure it will be seen that the material finds do not give any definite basis for an interpretation. The possibilities are numerous, but among them one appears to demand especial consideration. Within the area of the Mesopotamian civilisation two structures are known which can be adduced as possible parallels to the Barbar oval: the oval temple of Nin-Khursag at al- ᶜUbaid 7) and the temple oval at Khafājah, east of Baghdad 8), both of which are contemporary with the Barbar oval. The structures consist of cult-buildings, surrounded by one or more asymmetrical oval walls and connected with the surrounding structures by a ramp or a stairway. Although the two structures differ in important respects from the Barbar oval - they are, for example, somewhat larger, and the building material is different: "reddish brick" - they show in plan a certain measure of agreement, while they have also several details in common: both at Khafājah and at Barbar, at a time when the level outside the oval has been higher than that inside, drains have been constructed to prevent flooding within the wall; in the Nin-Khursag temple the walls were plastered (with clay) at a late period in the same way as the outer wall at Barbar, while on all three sites we find several plaster floors laid the one above the other. From the Khafājah oval 9), and moreover also from the Sin temple at Khafājah 10) and from the Shara temple at Tell Agrab 11), a series of cubical sacrificial tables is known, originally rounded at the top; these tables have not been actual altars, but merely blocks on which the sacrificial animals were slaughtered. The large cubical plaster block in the Barbar oval (Fig. 2G) resembles these sacrificial tables exactly. The possibility that the Barbar oval, like the contemporary oval temples of Mesopotamia, has had a cult function is supported to some degree by the objects found at Barbar; thus the remarkable broken beaker bases may have been used in cult ceremonies, while the numerous animal bones must be explained as the remains of sacrificial animals. In a survey of the Mesopotamian ovals P. Delougaz 12), the excavator of the Khafājah temple, states that the type appears to be found throughout Mesopotamia, though restricted in time to the Early Dynastic Period. As early as the close of the last century a basalt block was found in Bahrain bearing a cuneiform inscription mentioning the god lnzag 13), while from the introduction to two letters found at Nippur we know that lnzag - and probably in addition the Sumerian divinities Sin and Nin-Khursag - were worshipped in Dilmun 14), a locality which is often mentioned in Sumerian texts and which has in the course of the last few years been identified with ever greater certainty with Bahrain 15). It is possible that the temple oval at Barbar can be seen as yet another indication of prehistoric cultural connections between Mesopotamia and Bahrain. Peder Mortensen